The need to create awareness about autism - Danasekaran, Raja; Annadurai, Kalaivani; Mani, Geetha (International Journal of Contemporary Pediatrics, 2017)
Autism is a disorder of neural development characterized by a triad of impaired social interaction, impaired communication and restricted, repetitive or stereotyped behavior. The diagnostic criteria require that symptoms become apparent before a child is three years old. Autism affects information processing in the brain by altering how nerve cells and their synapses connect and organize. The prevalence of autism is about 1-2 per 1000 people worldwide and it occurs about four times more often in boys than girls. Parents usually notice signs in the first two years of their child's life. Early behavioral, cognitive or speech interventions can help autistic children gain self-care, social and communication skills.